Mitochondrial Telomerase Reverse Transcriptase Protects From Myocardial Ischemia/Reperfusion Injury by Improving Complex I Composition and Function. Issue 23 (7th December 2021) - Ale-Agha, Niloofar; Jakobs, Philipp; Goy, Christine; Zurek, Mark; Rosen, Julia; Dyballa-Rukes, Nadine; Metzger, Sabine; Greulich, Jan; von Ameln, Florian; Eckermann, Olaf; Unfried, Klaus; Brack, Fedor; et al.
Abstract : Background: The catalytic subunit of telomerase, telomerase reverse transcriptase (TERT), has protective functions in the cardiovascular system. TERT is not only present in the nucleus but also in mitochondria. However, it is unclear whether nuclear or mitochondrial TERT is responsible for the observed protection, and the appropriate tools are missing to dissect this. Methods: We generated new mouse models containing TERT exclusively in the mitochondria (mitoTERT mice) or the nucleus (nucTERT mice) to finally distinguish between the functions of nuclear and mitochondrial TERT. Outcome after ischemia/reperfusion, mitochondrial respiration in the heart, and cellular functions of cardiomyocytes, fibroblasts, and endothelial cells, as well, were determined. Results: All mice were phenotypically normal. Although respiration was reduced in cardiac mitochondria from TERT-deficient and nucTERT mice, it was increased in mitoTERT animals. The latter also had smaller infarcts than wild-type mice, whereas nucTERT animals had larger infarcts. The decrease in ejection fraction after 1, 2, and 4 weeks of reperfusion was attenuated in mitoTERT mice. Scar size was also reduced and vascularization increased. Mitochondrial TERT protected a cardiomyocyte cell line from apoptosis. Myofibroblast differentiation, which depends on complex I activity, was abrogated in TERT-deficient and nucTERT cardiac fibroblasts and completely restored in mitoTERT cells. In endothelial cells, mitochondrial TERT enhanced migratory capacity and activation of endothelial nitric oxide synthase. Mechanistically, mitochondrial TERT improved the ratio between complex I matrix arm and membrane subunits, explaining the enhanced complex I activity. In human right atrial appendages, TERT was localized in mitochondria and there increased by remote ischemic preconditioning. The telomerase activator TA-65 evoked a similar effect in endothelial cells, thereby increasing their migratory capacity, and enhanced myofibroblast differentiation. Conclusions: Mitochondrial, but not nuclear TERT, is critical for mitochondrial respiration and during ischemia/reperfusion injury. Mitochondrial TERT improves complex I subunit composition. TERT is present in human heart mitochondria, and remote ischemic preconditioning increases its level in those organelles. TA-65 has comparable effects ex vivo and improves the migratory capacity of endothelial cells and myofibroblast differentiation. We conclude that mitochondrial TERT is responsible for cardioprotection, and its increase could serve as a therapeutic strategy. Abstract : Supplemental Digital Content is available in the text.